India : Power Supply to Agriculture, Volume 4. Methodological Framework and Sampling Procedures Report - World Bank (Washington, DC, 2013)
After almost a decade of high-level effort to bring the charges (tariffs) that farmers pay for electricity more nearly into line with the costs of supply, India has barely made a dent in the longstanding and increasingly uneconomical practice of subsidizing power to agricultural consumers for irrigation. Progress has been slowed by the understandable but misplaced concern that higher tariffs would harm farmers--and that the injured parties would take political revenge on the reformers. This study seeks to dispel that anxiety. It is the result of a joint effort by the Bank and the states of Haryana and Adhra Pradesh , both of which have begun raising the price of electriicity to agriculture. Its central contribution to policy discussion is the detail in which it documents the costs--ususally neither acknowledged nor clearly defined--to farmers in those states of subsidies that actually harm agricultural operations more than they help as well as the benefits that the farmers would get from improved quality of electricity services. The costs--in power outages, damaged pumping equipment, irrigation foregone because of power losses, distorted investment patterns, among others--exact a heavy toll from ordinary farmers. In the form of deficits, the subsidies also sap state budgets of funds that could otherwise be invested in rural infrastructure, extension services, and advanced agricultural technology. As unrecovered costs, they starve suppliers of funds for maintenance and improved service. On the other side of the coin lie the benefits that reliable flows of power and good quality of other electricity services could deliver to rural India.